Island biogeography: patterns of marine shallow‐water organisms in the Atlantic Ocean. (1st July 2015) - Hachich, Nayara F.; Bonsall, Michael B.; Arraut, Eduardo M.; Barneche, Diego R.; Lewinsohn, Thomas M.; Floeter, Sergio R.
Abstract Aim The aim of this study was to understand whether the large‐scale biogeographical patterns of the species–area, species–island age and species–isolation relationships associated with marine shallow‐water groups in the Atlantic Ocean vary among marine taxa and differ from the biogeographical patterns observed in terrestrial habitats. Location Atlantic Ocean. Methods Reef fish, gastropod and seaweed species richness as well as reef fish endemic species data were obtained for 11 Atlantic oceanic islands. Using a multimodel inference approach based on linear and nonlinear regressions, we tested hypotheses regarding the variation in species richness and endemism as a function of island area, age and isolation. Best models were selected using ratios between Akaike weights corrected for small sample size (AICc). Results were compared between the three shallow‐water species groups and contrasted against previous studies of marine and terrestrial systems. Results Island area was the best single predictor of gastropod and seaweed richness, although it was not an improvement compared to the null model for reef fish. Island age explained richness in all taxa and was the best single predictor of reef fish richness. Isolation was a good predictor of seaweed richness but not of fish and gastropod richness, possibly because of their overall higher dispersal capacity. Reef fish endemism was influenced solely by island isolation. Main conclusions This work reveals large‐scale island biogeographical patterns for marine shallow‐water organisms in the Atlantic Ocean. Our results suggest that reduced gene flow is a potentially important mechanism for the maintenance of reef fish endemism in oceanic islands. The role of island age regarding the species richness of all taxa emphasizes the importance of habitat history for the geographical distribution of marine shallow‐water biodiversity. Finally, we show that some island biogeographical patterns differ not only between marine and terrestrial ecosystems but also, importantly, within marine shallow‐water environments, where the biogeographical patterns are highly taxon‐dependent.